Social networks and teaching skills – Learning of the XXI Century - Sánchez-Pacheco, Carlos Luis (2020)
Education in the 21st century highlights globalization and internationalization. Teachers in the 21st century are perceived to be experts in technology, effectively involve and teach students of the Z generation. Educational institutions must be equipped with a prerequisite for ICT resources, both in hardware and software, and The curricula are designed to promote a collaborative environment centered on the student. This study determines the skills of the 21st century that teachers possess in terms of social networks, remembering that they still need guidance to use technology safely and effectively.